Beetle Bits — The Science of Paleoentomology - Morgan, Alan; Morgan, Anne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1980)
Summary Several Quaternary sequences in North America have been analysed for fossil insects. Most of the insect remains are from beetles, and these are rapidly becoming recognised as very reliable indicators of climatic and vegetational changes. Like pollen they are present in most Quaternary deposits, but unlike most pollen grains they can be identified specifically. Also, beetles appear to respond rapidly to climatic change illustrating thermal variations which are often not detected by other conventional indicators. This paper briefly summarises some of the techniques and results of work in Canada, parts of the United States and England.